Kultura klasy robotniczej w warunkach kryzysu społeczno-gospodarczego. Uwagi teoretyczne - Żygulski, Kazimierz (Wydział Prawa i Administracji UAM, 1988)
The main problem considered in the article is the influence of the socioeconomic crisis on the working-class culture. The 1929 - 1933 crisis brought about a decrease in real incomes of employed workers, a decrease in buying force of money what in turn resulted in changes in workers' family budgets. Cultural expenses, expenditure on press, movies, books were either drastically reduced or eliminated at all. Research on workers family budgets in those years indicates that expenses on culture belonged to a group of needs covered with the smallest minimal part of income. With respect to the unemployed, various social, philantropic and charity institutions attempted to create for them some possibilities of participation in cultural life through establishing clubs, community centers or libraries. However, those efforts were a limited success, since they were sometimes regarded by the unemployed as attempts to create a substitute for cultural life, attempts to create appearances of care. The Polish socio-economic crisis of the '80 deeply infringed upon the established rhythm of a worker's life, including the rhythm of his cultural life. The latter is determined by days-off, holidays and the rhythm of mass-media with television and its regular programmes in the forefront. The crisis infringes upon those rhythms in various ways, usually to the detriment of cultural life, which becomes reduced and incidental. However, the crisis results in a significant deterioration of material status of workers, making them reduce all expenses. In effect, the expenses on culture drop to a remote place in the hierarchy of expenditure in family budgets. The issue of workers' participation in cultural life includes also other problems which became evident in recent years and which are subject to analysis in the last part of the article. To those problems belong: a) a decrease in production of cultural goods and market shortages of such goods (in such cases workers have the smallest chance of purchase); b) the sharpening of relations between groups and the revival of latent conflicts (it brings to light moral problems of social life); c) the dissemination of exaggerated images of remote and rich countries where it is easy to find good jobs and pay; d) an increased interest in the past and frequentidealizations of that past. Despite its negative influence on cultural life of workers, the crisis acts also as a stimulus for the workers' own creation. In recent years workers' literary, theatrical and musical activity, to a smaller extent their fine arts production, have been considerably intensified. The said creativity reflects contemporary problems experienced by various workers' communities and therefore it is an important document of our times.
The working-class culture in conditions of socio-economic crisis. Theoretical remarks